The Relationship Between the Stay‐Green Trait and Grain Yield in Elite Sorghum Hybrids Grown in a Range of Environments - Jordan, D. R.; Hunt, C. H.; Cruickshank, A. W.; Borrell, A. K.; Henzell, R.G. (Crop science, 2012)
ABSTRACT The stay‐green drought adaptation mechanism has been widely promoted as a way of improving grain yield and lodging resistance in sorghum [Sorghum bicolor (L.) Moench] and as a result has been the subject of many physiological and genetic studies. The relevance of these studies to elite sorghum hybrids is not clear given that they sample a limited number of environments and were conducted using inbred lines or relatively small numbers of experimental F1 hybrids. In this study we investigated the relationship between stay‐green and yield using data from breeding trials that sampled 1668 unique hybrid combinations and 23 environments whose mean yields varied from 2.3 to 10.5 t ha−1. The strength and direction of the association between stay‐green and grain yield varied with both environment and genetic background (male tester). The majority of associations were positive, particularly in environments with yields below 6 t ha−1. As trial mean yield increased above 6 t ha−1 there was a trend toward an increased number of negative associations; however, the number and magnitude of the positive associations were larger. Given that post‐flowering drought is very commonly experienced by sorghum crops world wide and average yields are 1.2 and 2.5 t ha−1 for the world and Australia, respectively, our results indicate that selection for stay‐green in elite sorghum hybrids may be broadly beneficial for increasing yield in a wide range of environments.